Soil temperature effects on nitrogen fixation and growth of Stylosanthes gracilis Pueraria javanica - Souto, Sebastião Manhães; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
In two greenhouse experiments with several varieties of Stylosanthes gracilis H.B.K. and Pueraria javanica (Roxb.) Benth. the effects of excessive soil temperatures and of seed pelleting with rockphosphate on the establishment of the symbiosis and on forage production were studied. In both forage species there was a significant interaction of soil temperature and variety, indicating varying responses to the high soil temperatures. Nodulation and growth of two Brazilian varieties Deodoro I and II, a variety introduced by F.A.O. (13.381) of S. gracilis, were stimulated by soil temperatures normally considered excessive (34°C mean of daily maxima). Three other varieties grow better at lower soil temperatures (29°C mean of daily maxima). With P. javanica one variety (I.A.C.) was stimulated and three varieties injured by the higher soil temperatures. With S. gracilis effects of double seed pelleting with rockphosphate also varied with the varieties. With the varieties Deodoro I and II and Senegal N-6399, nodulation and nitrogen fixation were stimulated but not with the three other varieties. With P. javanica effects of seed pellets were dependent on soil temperatures, nodule weight increased by the higher soil temperature with double seed pelleting, but not with simple pellets. With P. javanica total plant nitrogen showed a highly significant correlation (r = 0,95) with nodule weight while with S. gracilis there was no correlation at all, of these two factors.